Fashionable nihilism : a critique of analytic philosophy - Wilshire, Bruce W. (State University of New York Press, 2002)
"Thoreau wrote that we have professors of philosophy but no philosophers. Can't we have both? Why doesn't philosophy hold a more central place in our lives? Why should it? Eloquently opposing the analytic thrust of philosophy in academia, noted pluralist philosopher Bruce Wilshire answers these questions and more in an effort to make philosophy more meaningful to our everyday lives. Writing in an accessible style he resurrects classic yet neglected forms of inquiring and communicating. In a series of personal essays, Wilshire describes what is wrong with the current state of philosophy in American higher education, namely the cozy but ultimately suffocating confinements of professionalism. He reclaims the role of the philosopher as one who, like Socrates, would goad us out of self-contentedness into a more authentic way of being and knowing."--Jacket